When conflict resolution fails an alternative to negotiation and dialogue : engaging radical disagreement in intractable conflicts - Ramsbotham, Oliver (Polity Press, 2017)
Bringing warring parties to the negotiating table is the aim of any peace process. But what happens when those negotiations falter and conflict resolution fails? Is everything lost or are there prospects for meaningful change in even the most intractable of conflicts?In this insightful book, leading scholar-practitioner in conflict resolution Oliver Ramsbotham explores the phenomenon of radical disagreement as the main impediment to negotiation, problem solving and dialogue between conflict parties. Taking as his focus the long-running and seemingly irresolvable conflict between Israel and Palestine, he shows how what is needed in these circumstances is not less radical disagreement, but more. Only by understanding what is blocking the way and by promoting collective strategic engagement within, across and between the groups involved, can deadlock be transformed.Rich in detail and accessibly written, this book introduces a new and as yet relatively unexplored frontier in conflict studies. Its wider application to other phases, levels and war zones holds out rich promise for extending conflict engagement in some of the world?s deadliest and most difficult hot spots.